THE INFLUENCE OF CONTENT QUALITY ON WILLINGNESS TO PAY A PREMIUM PRICE FOR VIDEO STREAMING SERVICES: THE MEDIATING ROLE OF BRAND TRUST AMONG VIU USERS IN INDONESIA - Rosnaeni; Hidayanti, Ida; Zain, Zandy Pratama (Journal of Management and Islamic Finance, 2025)
This study aims to determine the effect of content quality on willingness to pay a premium price through brand trust among Viu users in Indonesia. This research is quantitative research. The population in this study are users of Viu premium in Indonesia. The number of samples in this study were 119 respondents. The data was processed using the Structural Equation Modeling (SEM) with Smart Partial Least Square (Smart-PLS) version 4.0 as a statistical program. The results of this study show that, content quality does not directly influence willingness to pay a premium price. Meanwhile, content quality positively and significantly effect on brand trust, which in turn significantly drives consumers' willingness to pay a premium price. This research demonstrates brand trust's crucial mediating role. The implications of this study highlight the importance of a strategic approach for video streaming service providers that not only focuses on content quality but also on building and maintaining brand trust. This can be achieved through marketing strategies that emphasize core brand values, such as transparency, reliability, and a commitment to quality, as a strategy to increase willingness to pay premium price.